2012
DOI: 10.1088/0964-1726/21/4/045007
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical characterization of bucky gel morphing nanocomposite for actuating/sensing applications

Abstract: Since the demonstration of the bucky gel actuator (BGA) in 2005, a great deal of effort has been exerted to develop novel applications for this electro-active morphing nanocomposite. This three-layered bimorph nanocomposite can be easily fabricated, operated in air and driven with a few volts. The BGA with improved mechanical strength is an excellent candidate for application in macro- to micro-scale smart structures with actuating and sensing capabilities. However, developing new applications requires identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 31 publications
(32 reference statements)
0
11
0
Order By: Relevance
“…On the downside, the electromechanical response of IEAPs is also known to be dependent on ambient parameters such as humidity and temperature [34,36]. Issues of repeatability can emerge due to viscoelastic creep that depends both on the temperature of the environment as well as the heating induced by the actuator's driving signal [37][38][39][40]. The performance of IEAP actuators has been reported to change both because of repeated work-cycles as well as the spontaneous deterioration [23,41].…”
Section: Open Accessmentioning
confidence: 99%
“…On the downside, the electromechanical response of IEAPs is also known to be dependent on ambient parameters such as humidity and temperature [34,36]. Issues of repeatability can emerge due to viscoelastic creep that depends both on the temperature of the environment as well as the heating induced by the actuator's driving signal [37][38][39][40]. The performance of IEAP actuators has been reported to change both because of repeated work-cycles as well as the spontaneous deterioration [23,41].…”
Section: Open Accessmentioning
confidence: 99%
“…It was shown that functionalized carbon nanotube (CNT) by aromatic diamine , crosslinked super‐growth CNTs , and multi‐walled CNT improved the BGA performance significantly. Lastly, the effects of geometrical parameters on the mechanical properties of the BGA were studied and it was shown that using thinner BGA resulted in the higher curvature of bimorph.…”
Section: Introductionmentioning
confidence: 99%
“…Mechanical characterization of BGA via nanoindentation and dynamical mechanical analysis has been reported by the authors. 10 BGA maximum lateral displacement, shelf life (change in displacement after being stored), and lifetime (change in displacement over time) has also been studied by our group to identify the effect of applied voltage and frequency, CNT type, thickness, and weight fraction of constituents. 11 On the basis of the later study, a displacement model was also developed for BGA samples made of different CNT and ionic liquid types.…”
Section: Introductionmentioning
confidence: 99%
“…To date, most research conducted on BGA has been focused on characterization and performance enhancement, rather than its applications. Mechanical characterization of BGA via nanoindentation and dynamical mechanical analysis has been reported by the authors .…”
Section: Introductionmentioning
confidence: 99%